Criação de valor para empresas prestadoras de serviços no ambiente virtual - Casartelli, Leonardo Vendramini (2017)
The way companies interact with their consumers has been changing deeply during the last few years. Internet, social networks and new digital marketing features have made it necessary for organizations to adapt themselves to this new context in order to remain market competitive while other companies have already presented new commercial models focused on digital market. Traditional sectors enterprises, such as weddings were also influenced. By means of gathering theoretical background and case studies, this survey has the purpose of analyzing the value creation for a wedding market brand which has been acting exclusively on the internet with the goals of identifying the main strategies and challenges of this sector recently. Drawing on digital marketing and social medias which creates value to the brand, iCasei is nationally known by your wedding webpages evolution in which the focus are improving the website itself as well as the wedding gift lists which can be converted into cash, what, as stated in this survey, makes a great difference due to its reliability and quality known by its consumers and that helps to go over challenges of a totally online services